Privatization in Emerging Economies: An Agency Theory Perspective - Dharwadkar, Bavi; George, Gerald; Brandes, Pamela (Academy of Management Review, 2000)
The ineffectiveness of several privatized firms within emerging economies underscores the importance of agency theory issues and their impact on the privatization-performance relationship. The authors argue that weak governance and limited protection of minority shareholders intensify traditional principal-agent problems (perquisite consumption and entrenchment) and create unique agency problems (expropriation). The authors suggest that postprivatization performance can be enhanced by using appropriate ownership, management, and corporate structures that mitigate agency problems in the context of weak governance, and they highlight avenues for research.